Aerobic exercise prescriptions on bone strength and postural stability: a scoping review - Shakiren, Saidatul Shamine (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Introduction – Aerobic exercise is generally beneficial to increase heart rate, stroke volume and improving individual physical fitness. Objective: This review aimed to clarify the findings on the effects of aerobic exercises specifically on strengthening the bone and enhancing the stability of body posture. Methodology – Literature was searched systematically based on PRISMA guidelines, using PubMed, Science Direct, Scopus and Springer Link databases from 2016 to 2021. All 15 articles on human randomised-controlled studies - were included in the final analysis. Out of 15, only three studies were found to investigate the effects of aerobic exercise on bone strength and postural stability. Meanwhile, only one study reported the effects of aerobic exercise on bone strength alone while another 11 studies reported improvements in postural stability. Type of aerobic exercises include walking exercises (e.g. Brisk walking), Thai-boxing dance, aquatic exercise therapy (water-based exercises), resistance and strength exercises, stabilisation exercises and also few forms of Tai Chi exercises. Based on the analysis, four studies reported that aerobic exercise indirectly develops muscular strength rather than bone strength while five studies reported improvement in reducing the risk of falling and avoid fall-related injuries. Thus, the type of exercises are suitable for healthy individuals are a set of combined exercises which consists of the elements of strength, balance and walking exercises whereas Tai Chi could be prescribed for the elderly population to enhance quality of life and prevent back pain injuries. Moreover, brisk walking exercise could be recommended to be Introduction – Aerobic exercise is generally beneficial to increase heart rate, stroke volume and improving individual physical fitness. Objective: This review aimed to clarify the findings on the effects of aerobic exercises specifically on strengthening the bone and enhancing the stability of body posture. Methodology – Literature was searched systematically based on PRISMA guidelines, using PubMed, Science Direct, Scopus and Springer Link databases from 2016 to 2021. All 15 articles on human randomised-controlled studies - were included in the final analysis. Out of 15, only three studies were found to investigate the effects of aerobic exercise on bone strength and postural stability. Meanwhile, only one study reported the effects of aerobic exercise on bone strength alone while another 11 studies reported improvements in postural stability. Type of aerobic exercises include walking exercises (e.g. Brisk walking), Thai-boxing dance, aquatic exercise therapy (water-based exercises), resistance and strength exercises, stabilisation exercises and also few forms of Tai Chi exercises. Based on the analysis, four studies reported that aerobic exercise indirectly develops muscular strength rather than bone strength while five studies reported improvement in reducing the risk of falling and avoid fall-related injuries. Thus, the type of exercises are suitable for healthy individuals are a set of combined exercises which consists of the elements of strength, balance and walking exercises whereas Tai Chi could be prescribed for the elderly population to enhance quality of life and prevent back pain injuries. Moreover, brisk walking exercise could be recommended to be practiced by patients from any age group in order to strengthen the bone and improve postural stability. Conclusion – Aerobic exercises significantly promote stability in body posture in almost all population targeted rather than reinforce bone strength especially in elderly. It is believed that bone formation is also restricted in the aging-related issues such as the decline of bone mineral density (BMD). Selection of types of exercise, duration of time and frequency is essential for optimal effect for individual health.